Analysis Of The Impact Of Tourist Visit Level On The Economy Of Local Communities In The Village Of Bena Village, Ngada District - Maria Endang Jamu; Yulius Laga (Universitas Muhammadiyah Sorong, 2021)
The traditional village of Bena has become a tourist destination in the Ngada district and is a nationally recognized tourist icon, even known globally. This traditional village is visited by many tourists, because of its uniqueness. The purpose of this research is to analyze the impact of tourist visits on the economy of lokal communities in the traditional village of Bena. This is important to be researched and analyzed because, the increasing interest of tourists, who come to visit the traditional village, has a positive impact, especially on the lokal economy. The approach used in this research is descriptive qualitative, with the data collection method is in-depth interviews. The informants in this study were lokal people around the tourist area. The results show that the increase in the number of tourist visits has had a positive impact on the lokal community in Bena Village, which includes an increase in community income from the sale of woven products, employment opportunities in tourism, business opportunities for lokal people, and side jobs. apart from being a farmer, and people's welfare which is getting better from year to year.